Gender recognition from face images - Wong, Kah Wai. (2011)
Face detection is a computer technology that concerns with finding if there are any faces in a given image (usually in gray scale) and returning the image location and content of each face if any. This is the first step of any fully automatic system that analyzes the information contained in faces. While earlier work dealt mainly with upright frontal faces, several systems have been developed that are able to detect faces fairly accurately with in-plane or out-of-plane rotations in real time. Face detection technology can also be used for other purposes such as gender recognition. This report aims to discuss on the use of face detection technology in the implementation of a gender recognition program as well as the process of how the face detection technology can be modified into that of a gender recognition program that determines the gender from frontal face images. This report will cover the background of face detection, the purpose and scope of this project, the literature review of the face detection framework, the process of carrying out the project and its results.